Assessment of Morphological and Functional State of Hematopoietic Progenitor Cells from Cord Blood for Potential Transplantation - Bilko, Denys I.; Borbulyak, Iryna Z.; Bilko, Nadiia M. (Problems of Cryobiology and Cryomedicine, 2013)
N/A Probl Cryobiol Cryomed 2013; 23(3):283–286.